Immune Response to Infection with Mycobacterium ulcerans - Gooding, Travis M. (American Society for Microbiology, 2001)
Mycobacterium ulcerans is a slow-growing, acid-fast bacillus that causes chronic necrotizing skin ulcers known as Buruli ulcers. Previously reported information on immunity to this mycobacterium is limited. We examined immune responses to M. ulcerans and M. bovis BCG in patients with M. ulcerans disease and in 20 healthy control subjects (10 tuberculin test positive and 10 tuberculin test negative). Cell-mediated immunity was assessed by stimulating peripheral blood mononuclear cells (PBMC) with whole mycobacteria and then measuring PBMC proliferation and the production of gamma interferon (IFN-γ). Humoral immunity was assessed by immunoblotting. PBMC from all subjects showed significantly greater proliferation and IFN-γ production in response to stimulation with living mycobacteria compared with killed cells. However, PBMC from subjects with past or current M. ulcerans disease showed significantly reduced proliferation and production of IFN-γ in response to stimulation with live M. ulcerans or M. bovis than PBMC from healthy, tuberculin test-positive subjects (P < 0.001) and showed results in these assays comparable to those of tuberculin test-negative subjects (P > 0.2). Serum from 9 of 11 patients with M. ulcerans disease, but no control subject, contained antibodies to M. ulcerans. The results indicate that patients with M. ulcerans infection mount an immune response to M. ulcerans as evidenced by antibody production, but they demonstrate profound systemic T-cell anergy to mycobacterial antigens. These findings may explain some of the distinct clinical and pathological features of M. ulcerans-induced disease.